2016
DOI: 10.1038/leu.2016.232
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental interactions between endothelial and lymphoma cells: a role for the canonical WNT pathway in Hodgkin lymphoma

Abstract: The interaction between vascular endothelial cells (ECs) and cancer cells is of vital importance to understand tumor dissemination. A paradigmatic cancer to study cell-cell interactions is classical Hodgkin Lymphoma (cHL) due to its complex microenvironment.The role of the interplay between cHL and ECs remains poorly understood. Here, we identify canonical WNT pathway activity as important for the mutual interactions between cHL cells and EC.We demonstrate that local canonical WNT signaling activates cHL cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…It was shown that the majority of classical HL (cHL) samples are positive for the activated form of GSK‐3β (Y216 phosphorylation), normally responsible for the inhibition of Wnt/β‐catenin signalling (Agostinelli et al ., ). Recently, a new insight was provided by results of studies that have functionally analysed local Wnt signalling in HL cells’ interactions with the micro‐environment (Linke et al ., ,b). These highlighted the importance of the autocrine Wnt‐5a/FZD 5 /DVL3/RHOA signalling axis in HL cell motility, chemotaxis and adhesion to endothelial cells (Linke et al ., ) and suggested that LEF1 and β‐catenin are required for chemotaxis in HL cells and their signalling to endothelial cells (Linke et al ., ).…”
Section: Similarities Between Cll and Lymphomas – Wnt‐biased Viewmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the majority of classical HL (cHL) samples are positive for the activated form of GSK‐3β (Y216 phosphorylation), normally responsible for the inhibition of Wnt/β‐catenin signalling (Agostinelli et al ., ). Recently, a new insight was provided by results of studies that have functionally analysed local Wnt signalling in HL cells’ interactions with the micro‐environment (Linke et al ., ,b). These highlighted the importance of the autocrine Wnt‐5a/FZD 5 /DVL3/RHOA signalling axis in HL cell motility, chemotaxis and adhesion to endothelial cells (Linke et al ., ) and suggested that LEF1 and β‐catenin are required for chemotaxis in HL cells and their signalling to endothelial cells (Linke et al ., ).…”
Section: Similarities Between Cll and Lymphomas – Wnt‐biased Viewmentioning
confidence: 99%
“…Recently, a new insight was provided by results of studies that have functionally analysed local Wnt signalling in HL cells’ interactions with the micro‐environment (Linke et al ., ,b). These highlighted the importance of the autocrine Wnt‐5a/FZD 5 /DVL3/RHOA signalling axis in HL cell motility, chemotaxis and adhesion to endothelial cells (Linke et al ., ) and suggested that LEF1 and β‐catenin are required for chemotaxis in HL cells and their signalling to endothelial cells (Linke et al ., ). The HL cells were shown to produce extracellular factors in a LEF1‐ and β‐catenin‐dependent manner, which affected the migration, sprouting and tube formation of the endothelial cells normally present in their micro‐environment.…”
Section: Similarities Between Cll and Lymphomas – Wnt‐biased Viewmentioning
confidence: 99%
“…This complex has been revealed to be very important in lung carcinogenesis [86]. In addition, Linke et al (2017) have indicated that in cases of Hodgkin's lymphoma, Wnt activates malignant cell chemotaxis towards the blood vessels as well as the local process of angiogenesis [87].…”
Section: F Wnt/b-cateninmentioning
confidence: 99%
“…Notably, Fzd7, one of the major receptors, was upregulated along the Wnt/β-catenin signaling pathway, and showed the greatest difference in expression as compared with other members of Fzd protein family [14,15]. Moreover, Fzd7 has been con rmed to play a key role in stem cell biology, cancer development and progression, and always be associated with poor patient prognosis and tolerance to chemotherapy treatment [16,17]. Hence, Fzd7 shows promise as a biomarker and a potential therapeutic target for TNBC.…”
Section: Introductionmentioning
confidence: 99%